Substrate Dielectric Constant Effects on the Performances of a Metasurface-Based Circularly Polarized Microstrip Patch Antenna - Kedze, Kam Eucharist; Wang, Heesu; Park, Yong Bae; Park, Ikmo (International Journal of Antennas and Propagation, 2022)
This paper presents the effects of substrate dielectric constants on the performance characteristics of a circularly polarized (CP) metasurface-based patch antenna. The antenna structure is a modified patch with a step-like truncation sandwiched between a metasurface composed of a 4 × 4 lattices of periodic metallic patches and a ground plane. The effects on the performance variations are evaluated for two principal cases that include a uniform dielectric constant and a nonuniform dielectric constant for the upper and lower substrates of the antenna. Through careful computational analysis, the effects of the substrate dielectric constant on the antenna performance in terms of bandwidth and gain were investigated, and the results demonstrate that the antenna performance improves with a decrease in the substrate dielectric constant. For a uniform substrate material with dielectric constants of ϵr1 = ϵr2 = 2.2, the fabricated antenna with an overall size of 54 mm × 54 mm × 3.0 mm (0.76o × 0.76o × 0.042o at 4.24 GHz) demonstrates the following measured performance characteristics: a -10 dB impedance bandwidth of 3.75-5.24 GHz (33.14%), a 3 dB axial ratio (AR) bandwidth of 3.85-4.64 GHz (18.61%), a radiation efficiency >93%, and a peak gain of 8.96 dBic within the AR bandwidth.
Keywords: Antenna performance; Antenna structures; Axial ratio bandwidth; Circularly-polarized; Ground planes; Metallic patches; Metasurface; Performance; Performance characteristics; Polarized microstrip patch antennas